A Game-Theoretic Framework for a Next-Generation Retail Power Market with a Large Number of Distributed Residential Electricity Suppliers (International Journal of Innovative Research in Computer Science & Technology, 2022)
This study provides a novel a system  dynamics foundation for this next retail electricity industry  (the "Energy Network") with both a large number of  dispersed household electricity providers (the "Energy  Cells"). The projected Energy Internet is intended to  facilitate the development of something like a wide range of  diverse renewable energy generating and storage devices  using plug-and-play technology. By running and  maintaining his respective regional generation, regional fuel  cells, including distributed generation tasks locally, cable  subscribers, also based on Energy Mitochondria, may be  simultaneous consumers and providers of power. This work  provides a collection of computer simulations of retailer  electric industry players, despite a variety of local and  worldwide restrictions. A statistical empirical study is  undertaken using tournament methodologies to develop an  efficient last retail power economic system. Your  computational showed that the developed equilibrium wage  approach is successful with a substantial penetration of  distribute household power providers
Keywords: Distribution System; Energy Management; Game Theory; Renewable Energy; Smart Grid